The evolution of DREAMS: using data for continuous program improvement. (15th June 2022) - Saul, Janet; Toiv, Nora; Cooney, Caroline; Beamon, Ta'Adhmeeka; Borgman, Mary; Bachman, Gretchen; Akom, Eniko; Benevides, Regina; Limb, Annaliese; Sato, Kimi; Achrekar, Angeli; Birx, Deborah
Abstract : The DREAMS (Determined, Resilient, Empowered, AIDS-Free, Mentored, and Safe) Partnership, a public-private partnership launched by the United States President's Emergency Plan for AIDS Relief (PEPFAR), represents the largest investment in comprehensive HIV prevention for adolescent girls and young women (AGYW) ever made in a single global initiative. This paper describes the evolution of programming over time using the triangulation of multiple data sources to develop and refine an impactful program, as well as to improve efficacy and resource investment. Methods of analysis used to evolve this programming include reviews of literature on behavioral, biomedical and structural interventions, and HIV vulnerability; PEPFAR program data; external implementation science and impact studies;observations from site visits; in-depth reviews of program materials; and inputs from AGYW and other stakeholders. Key program improvements made in response to this real-time data use are described, including the rationale for programmatic changes and the evidence base for continual program refinements. This review emphasizes the importance and process of implementing the most effective combination of structural and biomedical HIV prevention programming, based on the best available science, while also adapting to local context in a way that does not compromise effectiveness or violate core implementation principles. Data from research and evaluation are critical to move the HIV prevention field toward more impactful and efficient programming responsive to the lived realities of AGYW. A central tenant to using these data sources effectively is the inclusion of AGYW in decision-making throughout the planning and implementation of programming.